A collaboration between Rubens and Snyders on the pictorial representation of ophidians.: Three works with snakes by Snyders displayed in museums in Madrid. - Yubero-Hierro, Saúl (Eikón / Imago, 2025)
The collaboration between Rubens and Snyders was very fruitful, but doubts sometimes arise as to the hands that collaborated with the author of Head of Medusa, as Rubens retouched his own and others’ works. Three canvases with snakes portrayed by Snyders are exhibited in museums in Madrid. The aim is to contribute to the hypothesis of collaboration in that painting.